Causal effects of gut microbiome on hypertension: a Mendelian randomization study - He, Gang; Cao, Yu; Wang, Houzhao; Lv, Xiaoying (Frontiers in Microbiology, 2023)
Background: Previous observational study have shown that there is an important relationship between gut microbiota and hypertension, but whether there is a causal relationship between them has not been clarified. Methods: We obtained significant single nucleotide polymorphisms related to gut microbiota and hypertension from publicly available genome-wide association studies for a two-sample mendelian randomization study. The inverse-variance weighted meta-analysis is the main analytical method for evaluating causal relationships, and the mendelian randomization research results have been validated through a series of sensitivity analyses. Results: The inverse-variance weighted analysis results indicated that phylum Verrucomicrobia (OR:0.831, 95%CI:0.710-0.972; p=0.021), family BacteroidalesS24.7group (OR:0.672, 95%CI:0.496-0.911; p=0.01), family Bifidobacteriaceae(OR:0.709, 95%CI:0.569-0.884, p=0.002), genus Adlercreutzia(OR: 0.991, 95%CI: 0.982-0.999, P=0.035), genus Phascolarctacterium (OR:0.819, 95%CI:0.685-0.981; p=0.03), genus LachnospiraceaeNK4A136group (OR:0.990, 95%CI:0.981-0.999; P=0.025), and genus Ruminococcus2(OR:0.988, 95%CI:0.979-0.997; p=0.008) had protective causal effects on hypertension. The Family Alcaliginaceae(OR:1.011, 95%CI:1.000-1.021, p=0.04), Genus Anaerostipes(OR:1.375, 95%CI:1.096-1.653; p=0.025), Genus Collinsella(OR:1.899, 95%CI:1.361-2.348; p=0.02), and Genus Lachnospiraceae_UCG_010(OR:1.536, 95%CI:1.072-2.202; p=0.019) were associated with a higher risk of HTN. The reverse mendelian randomization analysis results showed no reverse causal relationship between HTN and these bacterial taxa. Conclusions: Our mendelian randomization analysis results indicate a potential causal relationship between these bacterial taxa and hypertension, providing a new perspective for the treatment and prevention of hypertension.